Are high school girls' lacrosse players at increased risk of concussion because they are not allowed to wear the same helmet boys' lacrosse players are required to wear? - R. Dawn Comstock; Alan T. Arakkal; Lauren A. Pierpoint; Sarah K. Fields (BMC, 2020)
Abstract Background Boys' lacrosse (LAX), a full contact sport allowing body and stick checking, mandates hard shell helmets with full face masks. Girls' LAX, which prohibits body checking and whose sphere rule is supposed to prevent stick checking to the head, allows optional flexible headgear with/without integrated eye protection. Whether the required boys' LAX helmets should also be mandated in girls' LAX has been debated. Methods In this retrospective cohort study we used LAX concussion data from a national high school sports-related injury surveillance study to determine if girls' LAX players were at increased risk of concussion from stick or ball contact due to differences in helmet regulations by calculating the attributable risk and attributable risk percent (AR%) for concussion resulting from ball or stick impacts. Results From 2008-09 through 2018-19, boys' LAX players sustained 614 concussions during 1,318,278 athletic exposures (AEs) (4.66 per 10,000 AEs) and girls' LAX players sustained 384 concussions during 983,291 AEs (3.91 per 10,000 AEs). For boys, athlete-athlete contact was the most common mechanism of concussion accounting for 66.4% of all concussions, while stick or ball contact accounted for 23.5%. For girls, stick or ball contact accounted for 72.7% of all concussions, while athlete-athlete contact accounted for 19.8%. Concussion rates from stick or ball contact were significantly higher in girls vs. boys (RR = 2.60, 95% CI 2.12-3.18). The attributable risk associated with playing girls' vs. boys' LAX for concussion resulting from stick or ball contact was 1.75 concussions per 10,000 AEs (95% CI 1.37-2.12) and the AR% was 61.5% (95% CI 52.9-68.5). An estimated 44.7% of all girls' LAX concussions could have been prevented if girls' LAX players wore the helmet mandated in boys' LAX. Conclusions Girls' LAX players who are allowed, but not required, to wear a flexible headgear are at increased risk of concussions from stick or ball impacts compared to boys' LAX players, who are required to wear a hard shell helmet with full face mask. Additional research is needed to determine if there are any defendable arguments to continue justifying restricting girls' LAX players access to this effective piece of protective equipment.